2022
DOI: 10.1200/jco.20.03452
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Randomized Study of CMB305 and Atezolizumab Compared With Atezolizumab Alone in Soft-Tissue Sarcomas Expressing NY-ESO-1

Abstract: PURPOSE CMB305 is a heterologous prime-boost vaccination regimen created to prime NY-ESO-1–specific CD8 T-cell populations and then activate the immune response with a potent TLR-4 agonist. This open-label randomized phase II trial was designed to investigate the efficacy and safety of adding the CMB305 regimen to atezolizumab (anti–programmed death ligand-1 therapy) in comparison with atezolizumab alone in patients with synovial sarcoma or myxoid liposarcoma. PATIENTS AND METHODS Patients with locally advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 29 publications
0
29
0
1
Order By: Relevance
“…A phase I trial including 24 sarcoma patients only showed partial response in 1 patient and stable disease in 13 patients [109]. In line with these findings, a sequential phase II trial that explored the combination of this NY-ESO-1 vaccine with anti-PD-L1 treatment in 45 sarcoma patients observed a partial response and stable disease in one and 23 patients, respectively [110]. To further improve T cell activation upon antigen presentation by dendritic cells, combination therapy of TCR gene therapy and vaccination is currently being explored in the clinic (https://clinicaltrials.gov/ Identifier: NCT03450122.…”
Section: Response To Other Immunotherapeutic Agentsmentioning
confidence: 63%
“…A phase I trial including 24 sarcoma patients only showed partial response in 1 patient and stable disease in 13 patients [109]. In line with these findings, a sequential phase II trial that explored the combination of this NY-ESO-1 vaccine with anti-PD-L1 treatment in 45 sarcoma patients observed a partial response and stable disease in one and 23 patients, respectively [110]. To further improve T cell activation upon antigen presentation by dendritic cells, combination therapy of TCR gene therapy and vaccination is currently being explored in the clinic (https://clinicaltrials.gov/ Identifier: NCT03450122.…”
Section: Response To Other Immunotherapeutic Agentsmentioning
confidence: 63%
“…In recent decades, several targeted immunotherapies for carcinogenic CTAs have been developed, and these immunotherapies have been tested in preclinical and early clinical environments. At present, most clinical studies have focused on the treatment of melanoma-associated antigen A (MAGEA) and New York esophageal squamous cell carcinoma-1 (NY-ESO-1), including cancer vaccines targeting CTAs to prevent tumor occurrence and development, and monoclonal antibodies against CTAs and CAR-T designed based on CTAs [ 65 - 73 ]. Due to the late discovery of KK-LC-1, the reported treatments include vaccines, photodynamic therapy combined with new photosensitizers and TCR-T therapy ( Fig.…”
Section: Application Of Targeted Kk-lc-1 In Tumor Immunotherapymentioning
confidence: 99%
“…The immune correlates noted with increased T-cell and antibody responses could be due to CMB305 alone as was seen in the phase Ib trial. Therefore, improvement in OS in those exhibiting immune responses (see Fig 4 in Chawla et al 21 ) could be attributed to CMB305 alone. Even with the promising 2 PRs in the combination arm, the LV305 phase I study described above, which lacked the G305 adjuvant, produced a sustained PR.…”
mentioning
confidence: 98%
“…Therefore, this vaccination strategy produced B- and T-cell immune reactions on the cellular level that translated to stability but not tumor response. In the context of CMB305 producing a stable phenotype, in the article that accompanies this editorial Chawla et al 21 attempted to further boost the vaccine response comparing atezolizumab with a combination of atezolizumab with CMB305 in NY-ESO-1–expressing SS and MRCLS in a randomized phase II trial. They are commended for completing a study in two rare sarcomas using a novel strategy to advance previous treatment findings.…”
mentioning
confidence: 99%
See 1 more Smart Citation